Hybrid Sukuk and wealth preservation: aligning with Maqasid al-shariah principles in modern Islamic finance - Saied, Galal Mohamed A. Abdul; Awang, Mohd Daud; Ahmad, Sa’odah Binti (Wise Academia Research Solutions, 2024)
Hybrid Sukuk represents a revolutionary approach to Islamic finance, melding traditional Sukuk with innovative financial derivatives and striving for ethical wealth preservation in line with Maqasid Al-Shariah principles. This research, addressing a notable void in the literature, investigates the infusion of Maqasid Al-Shariah into hybrid Sukuk structures, a pressing exploration owing to the escalating prominence of such instruments in Islamic finance. Rooted in empirical and theoretical explorations, the study examines the convergence between Maqasid Al Shariah objectives and hybrid Sukuk, emphasising wealth conservation, Shariah adherence, and the pivotal role of Islamic scholars and Shariah advisors in ensuring ethical congruence. Utilising evaluating methodologies, including Fitch and Moody’s credit ratings, it scrutinises the alignment of hybrid Sukuk with Shariah mandates to protect and augment financial resources. The revelations from the study demonstrating the potential of hybrid Sukuk in maintaining wealth and Shariah compliance and highlighting the adaptability of Maqasid Al-Shariah in crafting ethical financial tools responsive to modern economic needs. The research enriches Islamic finance discourse, providing refined insights and underscoring the critical role of Maqasid Al-Shariah in developing ethically robust and socially beneficial financial instruments, promoting ethical and societal enhancements in Islamic finance and contributing to enduring economic stability and societal prosperity